The globalization of nothing / George Ritzer. - Ritzer, George (Pine Forge, 2003)
'The Globalization of Nothing' takes the subject of globalization in new directions, introducing terms such as 'grobalization'. The key conflict in the world today is viewed as that between the grobalization of nothing and the glocalization of something.